Consulting Spirit—A Doctor’s Experience with Practical Mediumship by Ian D. Rubenstein - Bobrow, Robert S. (Journal of Scientific Exploration, 2012)
A British general practitioner has written a book about his sortie into the world of spirits (known to the initiates as “spirit”), mediums, telepathy, psychic circles, ghosts and poltergeists, and all manner of matter that cannot be touched but only felt. A concatenation of coincidences nudges him gradually until his life becomes a tableau where the supernatural has become natural, yet business as usual is still transacted. These are not quite C. J. Jung’s “meaningful coincidences,” which were structured through a parallel world of archetypes, a collective unconscious, and a subtle universal order, although there are similarities. Dr. Rubenstein’s happenstances, such as two teenagers trying to steal his car and all that ensues, are rather described as impish intrusions from the spirit world: spirit guides and dead relatives trying to get his attention.